2019
DOI: 10.5829/ije.2019.32.01a.01
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vitamin B12 Production using Chlorella vulgaris

Abstract: Microalgae Chlorella Vulgaris is enriched in vitamin B12 and cobalt ion which is positioned in the center of the vitamin molecule. This study aimed to investigate how different concentrations of cobalt chloride salt affected the vitamin B12 production by utilizing CO2 gas, to assess C. vulgaris biomass. Therefore, Bold's basal medium used as the medium and 0.5, 1.5, 2 and 2.5 μM cobalt chloride salt was added to C. vulgaris culture. Under four cobalt chloride salt treatments, the best growth rate was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…produced vitamin B12, the biomass of Chlorella ellipsoidea co-cultured with Brevunmdimonas sp. was 0.5-3 times higher than that of Chlorella ellipsoidea alone (Jalilian et al, 2019;Park et al, 2008). This demonstrated that vitamin B12 provided by heterotrophic bacteria could promote algal growth in the symbiotic system of algae-bacteria, promoting algae photosynthesis.…”
Section: Introductionmentioning
confidence: 85%
“…produced vitamin B12, the biomass of Chlorella ellipsoidea co-cultured with Brevunmdimonas sp. was 0.5-3 times higher than that of Chlorella ellipsoidea alone (Jalilian et al, 2019;Park et al, 2008). This demonstrated that vitamin B12 provided by heterotrophic bacteria could promote algal growth in the symbiotic system of algae-bacteria, promoting algae photosynthesis.…”
Section: Introductionmentioning
confidence: 85%
“…Two cobalamin coenzyme 5′-deoxyadenosylcobalamin and methylcobalamin occurred in green alga C. vulgaris , and the addition of cobalamin significantly stimulated green alga growth (Watanabe et al, 1997 ). Moreover, C. vulgaris grown in Bold's basal medium supplemented with 2 and 2.5 μM CoCl 2 produced 166.23 and 173.32 μg vitamin B 12 per 100 g dry weight (Jalilian et al, 2019 ). Additionally, many algal species require different combinations of cobalamin, vitamin B 1 , and B 7 (Croft et al, 2005 ) as they do not have pathways to synthesize cobalamin or may use alternative cobalamin-independent routes bypassing the need for the vitamin (Cruz-Lopez and Maske, 2016 ; Yao et al, 2018 ).…”
Section: Cobalt Is Essential For Lower Plantsmentioning
confidence: 99%
“…C. vulgaris contains eleven essential vitamins that humans cannot synthesize, including vitamin A, vitamin B1 (thiamine), vitamin B2 (riboflavin), vitamin B3 (niacin), vitamin B5 (pantothenic acid), vitamin B6 (pyridoxine), vitamin B9 (folate), vitamin B12 (cobalamin), vitamin C, vitamin E, and vitamin K [ 165 - 168 ]. Also, minerals promote several biological functions in the human body.…”
Section: Valuable Compounds From Chlorellamentioning
confidence: 99%